2020
DOI: 10.1007/s11229-020-02892-w
|View full text |Cite
|
Sign up to set email alerts
|

The epistemic demands of friendship: friendship as inherently knowledge-involving

Abstract: Many recent philosophers have been tempted by epistemic partialism. They hold that epistemic norms and those of friendship constitutively conflict. In this paper, I suggest that underpinning this claim is the assumption that friendship is not an epistemically rich state, an assumption that even opponents of epistemic partiality have not questioned. I argue that there is good reason to question this assumption, and instead regard friendship as essentially involving knowledge of the other. If we accept this acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…We want to be seen by our friends, to be loved and accepted for who we are, not ignored in favour of a positive fantasy. Mason (2021) thus proposes a conception of friendship in which it inherently involves knowledge of the other, or a progressive movement towards such knowledge: '[F]riendship is an epistemically involved, knowledge-involving, state' (Mason, 2021(Mason, , p. 2449. Such a conception of friendship, she suggests, rules out the possibility that acting epistemically irresponsibly could make one a better friend.…”
Section: Worries About Epistemic Partialismmentioning
confidence: 99%
See 1 more Smart Citation
“…We want to be seen by our friends, to be loved and accepted for who we are, not ignored in favour of a positive fantasy. Mason (2021) thus proposes a conception of friendship in which it inherently involves knowledge of the other, or a progressive movement towards such knowledge: '[F]riendship is an epistemically involved, knowledge-involving, state' (Mason, 2021(Mason, , p. 2449. Such a conception of friendship, she suggests, rules out the possibility that acting epistemically irresponsibly could make one a better friend.…”
Section: Worries About Epistemic Partialismmentioning
confidence: 99%
“…Finally, some sceptics about epistemic partialism have suggested that it goes wrong from the start, by accepting a mistaken view of friendship. (See Badhwar (1993), Kawall (2013), Yao (2020), Mason (2021) and Dormandy (2022)). Friendship, these sceptics suggest, importantly involves relating to the other person as they really are.…”
Section: Worries About Epistemic Partialismmentioning
confidence: 99%
“…However, as I shall explain later, Kawall underestimates the role of the non-deliberative, highgrade cases of doxastic partiality. Mason (2021) suggests a different argument building on an idea of Iris Murdoch who thinks that love is (or involves) knowledge. To love someone involves knowing who they are as a person where this knowledge has as its objects the character traits, personal qualities, and deeply held values and beliefs of a friend.…”
mentioning
confidence: 99%